Visio Services Quick Guide - Malik, Sahil (Springer, 2015)
In this fast-paced 100-page guide, you’ll learn to load, display and interact with dynamic, data-powered Visio diagrams in SharePoint 2013 or Office 365. Visio Services Quick Guide gives you the tools to build anything from a simple project workflow to an organizational infrastructure diagram, powered by real data from SharePoint or SQL Server. Colleagues can load your diagrams entirely in the browser, meaning that a single Visio client installation is enough to get started. Readers with JavaScript experience will also find out how to get additional control over Visio diagrams using the JavaScript mashup API, and how to build a custom data provider. The final chapter covers some useful information on administering Visio Services.